Steps Towards a Realisation of the Right to Have a Nationality - Gerard-René de Groot; Guayasén Marrero González (LeXonomica, 2024)
International standards regarding the acquisition and loss of nationality are increasingly being developed by various international institutions. This paper focusses on standard setting (in particular by the United Nations, the Council of Europe and the European Union) with relevance for European countries. While international treaties on or including rules on nationality law are addressed, attention is also given to soft law instruments such as guidelines and recommendations. Moreover, several new standards have also emerged from the decisions of international courts. The authors conclude that all these rules have as result that the margin of appreciation for national governments and courts in matters related to nationality law matters is getting increasingly smaller.PovzetekRazlične mednarodne institucije vse bolj razvijajo mednarodne standarde glede pridobitve in izgube državljanstva. Ta članek se osredotoča na določanje standardov (zlasti s strani Združenih narodov, Sveta Evrope in Evropske unije), ki so pomembni za evropske države. Obravnavane so mednarodne pogodbe o pravu o državljanstvu ali vključno s pravili o njem, pozornost pa je namenjena tudi instrumentom mehkega prava, kot so smernice in priporočila. Poleg tega je več novih standardov nastalo tudi na podlagi odločitev mednarodnih sodišč. Avtorja ugotavljata, da je posledica vseh teh pravil, da se polje proste presoje nacionalnih vlad in sodišč v zadevah, povezanih s pravom o državljanstvu, vse bolj zmanjšuje.